Compression-sensitive magnetic resonance elastography - Hirsch, Sebastian; Beyer, Frauke; Papazoglou, Sebastian; Tzschaetzsch, Heiko; Braun, Juergen; Sack, Ingolf; Guo, Jing (Physics in Medicine and Biology, 2013)
Magnetic resonance elastography (MRE) quantifies the shear modulus of biological tissue to detect disease. Complementary to the shear elastic properties of tissue, the compression modulus may be a clinically useful biomarker because it is sensitive to tissue pressure and poromechanical interactions. In this work, we analyze the capability of MRE to measure volumetric strain and the dynamic bulk modulus (P-wave modulus) at a harmonic drive frequency commonly used in shear-wave-based MRE. Gel phantoms with various densities were created by introducing CO2-filled cavities to establish a compressible effective medium. The dependence of the effective medium's bulk modulus on phantom density was investigated via static compression tests, which confirmed theoretical predictions. The P-wave modulus of three compressible phantoms was calculated from volumetric strain measured by 3D wave-field MRE at 50 Hz drive frequency. The results demonstrate the MRE-derived volumetric strain and P-wave modulus to be sensitive to the compression properties of effective media. Since the reconstruction of the P-wave modulus requires third-order derivatives, noise remains critical, and P-wave moduli are systematically underestimated. Focusing on relative changes in the effective bulk modulus of tissue, compression-sensitive MRE may be useful for the noninvasive detection of diseases involving pathological pressure alterations such as hepatic hypertension or hydrocephalus. © 2013 Institute of Physics and Engineering in Medicine.
CRIS-Team Scopus Importer:2022-08-03